Unleashing the Competitive Advantage of Malaysian Private Housing Developers through Product Analysis - Jaafar, Mastura; Nuruddin, Azlan Raofuddin; Syed Abu Bakar, Syed Putra; Mohd Raslin, Faraziera (UKM, 2015)
Malaysian housing developers produce a range ofproducts that has the characteristics of being large, expensive and durable. Nonetheless, the protracted development process exposes the developer to a high level ofrisk Previous product development studies had focused on the technical elements of development rather than managerial aspects. This paper examines the contribution ofproduct characteristics to the competitive advantage o.lMalaysian private housing developers. Using semi-structured snowball interviews, this qualitative slucly aims to elucidate upon the success factors of private housing developers. Ten successful housing developers were chosen for this research. The findings suggest that successlul project management coupled with a product selling price that reflects the location, quality and innovative ness of the product, count toward the developers reputation and branding. This paper expands the academic housing development literature by providing specific and in-depth information on housing developer products in Malaysia.